2017
DOI: 10.18203/2394-6040.ijcmph20174223
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and its associated risk factors in young adults attending a tertiary care institute of Nagpur: a cross sectional study

Abstract: Background: Hypertension is a silent killer and global public health problem. With the advent of globalization affecting the lifestyle of the population, non-communicable diseases like hypertension, diabetes etc. is affecting the young adults (18 to 40 years). The aim of the study was to estimate the prevalence of hypertension and its associated risk factors among young adults (18 to 40 years) attending a tertiary care centre of Nagpur.Methods: This was a cross sectional study on 370 participants of age 18 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(32 reference statements)
2
5
2
Order By: Relevance
“…This study showed the prevalence of hypertension increases with an increase in age which is supported by previous literature [ 9 , 29 31 ]. The higher prevalence of hypertension among higher age groups may be attributed to a high workload and lack of physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed the prevalence of hypertension increases with an increase in age which is supported by previous literature [ 9 , 29 31 ]. The higher prevalence of hypertension among higher age groups may be attributed to a high workload and lack of physical activity.…”
Section: Discussionsupporting
confidence: 92%
“…In this study overweight and physical inactivity were found to be independent risk factors for developing hypertension. This finding was in line with previous reports from Uganda, India, Ethiopia and Nepal (Kiber et al, 2019;Awoke et al, 2012;Patil et al, 2017;Dhungana et al, 2016). Urbanization are associated with changes in dietary habits and sedentary lifestyle which lead to obesity and those are associated as contributing factors in the development of high blood pressure.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of hypertension considerably higher than what has been reported in previous study conducted in Bangladesh (Ahmed et al, 2014). In India The prevalence of hypertension was found to be 23.24% (Patil, Sahoo, Dhoble, Kherde & Inamdar, 2017) and in Nepal the prevalence was 32.5% (Dhungana, Pandey, Bista, Joshi & Devkota, 2016).…”
Section: Discussioncontrasting
confidence: 60%
“…[9] Kahar, from Gujrat in a state wide community based study reported the tobacco use among similar (18-34 year) aged individuals, similar for males while much higher in females than our findings (35% in males; 26% in females) [10] The study setting may be the cause of this explicit difference.…”
Section: Discussioncontrasting
confidence: 52%